Sovereignty and liberty : the foundations of power - Lev, Amnon (New York : Routledge, 2014)
'Sovereignty and Liberty: A Study of the Foundations of Power studies the place of law in the idea of liberty. Legal theorists and political scientists almost invariably consider the question of liberty as a matter of its more or less successful translation into politico-legal order, but in so doing they usually fail to consider the subtle mechanisms by which subjection to law informs the articulation of liberty. This book addresses the reasons why law lies at the heart of a democratic model of government in order to consider how shifts in the conception of human existence have led to a crisis of our faith in law's capacity to guarantee liberty. The book introduces two key concepts to explain the exercise of power: the idea of a faith in sovereignty and the idea of the survival society that has risen in the wake of the demise of sovereignty. Drawing on the work of key names in the study of sovereignty, power and liberty, including Thomas Hobbes, Georg Wilhelm Friedrich Hegel, Hans Kelsen and Carl Schmitt, this book investigates the modern attachment to sovereignty, and how subjection to it became a source of existential meaning. Offering controversial new insights into the implication of liberalism in sovereign power and the dissociation of sovereignty, this book will appeal to students and academics in law, politics, and across the social sciences'--
Includes bibliographical references and index.
Keywords: Sovereignty; Law -- Philosophy; Liberty